Perioperative Management of Direct Oral Anticoagulants in Intracranial Surgery. Issue 4 (October 2020) - Porter, John; Dinsmore, Judith
Abstract : The use of direct oral anticoagulants is increasing rapidly, because of perceived benefits over older agents, such as predictable pharmacokinetics and a reduced risk of bleeding. Elderly patients, who are more likely to be prescribed these drugs, are also presenting for neurosurgical procedures more often. The combination of these factors will result in neurosurgeons and neuroanesthesiologists encountering patients prescribed direct oral anticoagulants on an increasingly frequent basis. This review provides a summary of the current evidence pertaining to the perioperative management of these drugs, in the context of elective and emergency intracranial surgery. It highlights emerging therapies, including specific antidotes, as well as areas where the evidence base is likely to improve in the future.